2009
DOI: 10.1007/s10802-009-9376-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Physical and Relational Aggression in a School-Based Sample of Boys and Girls

Abstract: The current study investigated the patterns of aggressive behavior displayed in a sample of 282 students in the 4th through 7th grades (M age = 11.28; SD = 1.82). Using cluster analyses, two distinct patterns of physical aggression emerged for both boys and girls with one aggressive cluster showing mild levels of reactive aggression and one group showing high levels of both reactive and proactive aggression. Both aggressive clusters showed problems with anger dysregulation, impulsivity, thrill and adventure se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
89
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 63 publications
26
89
0
11
Order By: Relevance
“…In line with findings on patterns of aggressive behavior displayed in children, we expected that maternal distress and hostile parenting would be associated with physical aggressionand indirect aggression, but that some gender-differentiated parental risk patterns could emerge, particularly for indirectly aggressive boys [19]. These predictions were confirmed.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In line with findings on patterns of aggressive behavior displayed in children, we expected that maternal distress and hostile parenting would be associated with physical aggressionand indirect aggression, but that some gender-differentiated parental risk patterns could emerge, particularly for indirectly aggressive boys [19]. These predictions were confirmed.…”
Section: Discussionsupporting
confidence: 74%
“…Alternatively, parents' behavior may foster the use of indirect aggression only in some children but not in others. Indeed, reference [19] recently found gender-related differences in the emotional and cognitive profiles of indirectly aggressive children and hypothesized that the causes of indirect aggression in girls may be the same as the causes of physical aggression in both boys and girls whereas the causes of boys' indirect aggression may differ. Further research is needed to understand how parents may facilitate the early development of indirect aggression in both sons and daughters.…”
Section: B Emotional Distress and Hostile Parenting To Children's Agmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the delinquent group, proactive aggression was more related to an aggression bias, while reactive aggression related more to a tendency to interpret social ambiguous situations as negative. Earlier studies have demonstrated that especially proactive aggression relates to psychopathology [46][47][48]. Therefore the delinquent group may constitute a more psychiatric group of delinquents in which proactive aggression is especially related to an aggressive interpretation bias.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudios realizados en los últimos años han mostrado que un importante número de jóvenes y adolescentes manifiestan conductas agresivas reactivas o proactivas, al tiempo que otros manifiestan conjuntamente ambos patrones de agresión (López-Romero, Romero y González-Iglesias, 2011;Muñoz, Frick, Kimonis y Aucoin, 2008). De este modo, se ha planteado la existencia de grupos diferenciados de jóvenes y adolescentes que responderían de forma exclusiva o predominantemente con conductas agresivas de tipo reactivo o proactivo, por un parte, y otros jóvenes que manifestarían ambos patrones de respuesta en los que precisamente los niveles de agresividad y violencia suelen ser de mayor gravedad (Andreu, 2010;Barker, Tremblay, Nagin, Vitaro y Lacourse, 2006;Crapanzano, Frick y Terranova, 2010). Tabla 1.…”
Section: Introductionunclassified